Agenesis of the dorsal pancreas: a rare cause of insulin-dependent diabetes without abdominal pain. Issue 9 (March 2018) - Liang, Kaiyong; Ou, Xiaojuan; Huang, Xukai; Lan, Qunfang
Abstract: Rationale: Agenesis of the dorsal pancreas is a very rare condition with an unknown pathology and etiology, although it may be associated with autosomal dominant or X-linked dominant inheritance or retinoic acid and hedgehog signaling pathway alterations. This condition usually manifests with abdominal pain or pancreatitis, although some cases are asymptomatic. Approximately 50% of affected patients with this disorder present with hyperglycemia or various other anomalies. Patient concerns: We report the case of a 23-year-old Chinese woman who visited the Department of Endocrinology and Metabolism with insulin-dependent diabetes but no specific symptoms, signs, or other deformities. Severe diabetic retinopathy indicated a long period of hyperglycemia. Diagnosis: Agenesis of the dorsal pancreas was observed incidentally during the common diagnosis of diabetes, and the diagnosis was established using magnetic resonance imaging, diffusion-weighted imaging, and magnetic resonance cholangiopancreatography. Interventions: Following the diagnosis of diabetes, insulin replacement therapy was initiated at a dosage of up to 45 U per day. The patient's blood glucose level was monitored, and the insulin dosage was adjusted accordingly. Outcomes: The patient's blood glucose levels gradually normalized after insulin treatment and were subsequently maintained with intensive insulin therapy. Treatment for diabetic retinopathy was provided by the Ophthalmology Department. Lessons: Agenesis of the dorsal pancreas should be considered in a young patient diagnosed with diabetes who presents with obvious diabetes-related complications (e.g., renal, retinal, or neurological) inconsistent with the course of the disease or a history of other congenital anomalies. We recommend the routine use of computed tomography or magnetic resonance imaging when examining young patients with diabetes.